FAST‐id system for enrichment of cells with TALEN‐induced mutations and large deletions. (18th March 2014) - Tokumasu, Daisuke; Sakuma, Tetsushi; Hayashi, Yoko; Hosoi, Sayaka; Hiyama, Eiso; Yamamoto, Takashi
<x xml:space="preserve">Abstract</x> Transcription activator‐like effector nuclease (TALEN)‐mediated genome editing is a powerful technique for analyzing gene functions in various cells and organisms. At target loci, TALENs can not only introduce short insertions and deletions, but also yield large deletions through the use of two TALEN pairs. Here, we report easy and efficient methods for enrichment of cells with TALEN‐induced mutations and large deletions. First, we established the fluorescence‐activated sorting of TALEN‐induced deletions (FAST‐id) system that enabled fluorescence‐activated cell sorting‐mediated enrichment of cells with TALEN‐induced mutations. In the FAST‐id system, either EGFP or mCherry and TALENs were co‐expressed. Using dual fluorescence selection, both left and right TALEN‐expressing cells were easily concentrated, resulting in enrichment of TALEN‐mediated mutated cells. Next, to apply the FAST‐id system to enrichment of cells with large deletions, we developed the fast unification of separate endonucleases (FUSE) method for assembly of two TALENs into a single expression vector. Using the FUSE method, we easily obtained a TALEN pair‐expressing plasmid driven by a single promoter. By combining the FAST‐id system and FUSE method, cells with large deletions were efficiently enriched. To the best of our knowledge, this is the first report of enrichment of cells with TALEN‐induced large deletions.